Penilaian Kinerja dan Risiko Keuangan PT Garuda Indonesia (Persero) Tbk Melalui Analisis Rasio Keuangan - Anis Kamal; Bravo Sinukaban; Frans Zidane; Justin Fransiskus; Kristo Abner; Alvianus Kristian (Journal of Economics, Management, and Accounting, 2025)
This study aims to assess the financial condition and performance of PT Garuda Indonesia (Persero) Tbk during the 2020–2024 period, amid a major restructuring process triggered by the financial crisis that occurred during the COVID-19 pandemic. This study uses a quantitative descriptive approach with analysis of liquidity, activity, leverage, and profitability ratios. The results show that liquidity performance is below the aviation industry standard, namely a current ratio <200%, a quick ratio <100%, and a cash ratio <50%. The activity ratio (TATO) is also below 2x, reflecting suboptimal asset utilization. In terms of leverage, the debt-to-total-assets ratio is above 35%, the standard limit, thus reflecting a high funding structure burden. Meanwhile, profitability also shows fluctuating results: gross profit margins are below 30% and net profit margins are very poor in 2020–2021, improving significantly in 2022, but declining again in 2023–2024. The same pattern occurred with low returns on investment in 2020–2021, increasing in 2022, and then weakening again thereafter. Overall, these findings indicate that Garuda Indonesia's financial recovery after restructuring has not yet fully stabilized across all key indicators